Neck and Low Back Pain Among Dentistry Staff - Duygu Geler Külcü,; Gülçin Gülşen,; Tuba Çiğdem Altunok,; Davut Küçükoğlu,; Sait Naderi, (Archives of Rheumatology, 2010)
Objective: To assess low back pain (LBP) and neck pain (NP) frequency in dentistry personel and to assess associated factors with LBP and NP in dentistry. Materials and Methods: 206 subjects participated in this crosssectional study. Demographic properties, working conditions, NP and LBP frequency in several positions have been recorded. Subjects were assessed by Visual analogue scale (VAS) (0-10) pain scores, Neck Pain Disability Index (NPDI) and Roland-Morris LBP Questionnaire (RMQ). The relationship between working conditions and assessed parameters has been analyzed by Spearman correlation coefficient (0< r<1). Comparison between age groups (age below and above 25 yrs) were assessed by Student T test, Mann Whitney U test and chi-square test. Comparison among specialization groups were assessed by Kruskal-Wallis variance analysis and chi-square test. Results: Mean age of the subjects was 23.5±5.0 (57% female). There were correlations between weekly working hours and LBP frequency during standing (r=0.153) and walking (r=0.178), daily working hour and LBP frequency during walking (r=0.159). Duration worked at chair-side was inversely correlated with RMQ (r=-0.188) and NDI (r=0.271) scores. Duration worked by standing was related with RMQ (r=0.252), NDI (r=0.334), LBP (r=0.200) and NP-VAS scores (r=0.279). Duration worked by standing was related with NP and LBP frequency in all positions. There was no difference among specializations. NDI scores were higher in patients older than 25 years (p=0.043) but no difference was observed in terms of other parameters. Conclusion: Working duration and posture have important influences on NP and LBP in dentistry. (Turk J Rheumatol 2010; 25: 122-9)